Digital Teaching Materials of Logical Thinking - Oriented Exposition Text for X Graders of SMA/MA/SMK - Ningsih, Cucu Maryati; Kusmana, Suherli; Gloriani, Yusida (International Journal of Educational Research Excellence (IJERE), 2024)
This research aims to develop a logical thinking-oriented exposition digital teaching material product that is feasible and effective for Indonesian Language learning in grade X students of SMA/MA/SMK. This research uses a research and development method (Research and Development) with the ADDIE (Analysis Design Development Implementation Evaluation) model. Data collection in the study was carried out and analyzed descriptively, both quantitative and qualitative. The result of the design and development of this digital teaching material is a digital module in the form of pdf and a Flipbook consisting of a cover, concept map, learning objectives, until author biodata. It also contains materials in videos to practice listening, reading and writing that can be accessed in youtube by scanning the link. The results of product validation by language, material and media validators and practitioners stated that the digital teaching materials of logical thinking-oriented exposition texts for SMA/MA/SMK with a result of 80.79% mean "Feasible" to use. The results of the implementation of digital teaching materials for logical thinking-oriented exposition texts for 63 grade X students at SMAN 1 Gantar, SMAN 1 Gantar and MA Ma'had al-Zaytun, showed that there was a significant development between student learning outcomes before and after the use of digital teaching materials after being assessed using the T-Test (Paired sample Test), meaning "effective" for learning exposition text materials. Thus, digital teaching materials for logical thinking-oriented exposition texts for teachers and students of class X SMA/MA/SMK are feasible and effective in learning.